(untitled) (Environmental Smoke, 2020)
The necropsy is an action composed of several stages carefully organized and performed on a corpse, aiming to elucidate or confirm what happened to the animal, so that it would die. The autopsy performed on a turtle by the team of academics from the Veterinary Medicine course at UNINASSAU, was of great value in making it possible to better understand its cause of death. Many convalescent turtles are sent to specialized environments in order to have their health restored, but some unfortunately end up dying, due to the seriousness of their case. The necropsy is then performed to clarify, refute, confirm or even modify a diagnosis previously established. Each necropsy stage is performed with great responsibility, where the qualification of veterinary medicine students is of paramount importance for this specific purpose. The necropsy performed on this chelonian Lepidochelys olivacea, aimed to provide an active practice and present a range of scientific knowledge, which academics will deal with now or in their professional lives. The conclusion regarding the autopsy performed, revealed that the cause of death was due to a cranial laceration probably caused by a propeller of a motor boat.